DEVELOPMENT AND EVALUATION OF CREAM PREPARATION CONTAINING PHYTOSOME FROM AMLA FRUIT EXTRACT (PHYLLANTHUS EMBLICA L.) - RIDWAN, SUCILAWATY; HARTATI, RIKA; PAMUDJI, JESSIE SOFIA (International Journal of Applied Pharmaceutics, 2023)
Objective: This study aims to develop and evaluate the phytosome of Phyllanthus emblica L. fruit extract. Methods: The formation of phytosome was performed by using three methods, namely solvent evaporation, antisolvent, and thin layer formation method. The phytosome was evaluated for its entrapment efficiency, particle size, polydispersity index, Fourier Transform Infra-Red (FTIR), and Transmission Electron Microscope (TEM) methods. The phytosome was made into cream with a concentration of 1%. The cream stability was evaluated at a room temperature of 40 °C for 28 d. The permeation of the total phenolic content of cream-containing phytosome and cream-containing extract without phytosome technology was evaluated by diffusion studies. Results: The best method to prepare phytosome was an antisolvent method with the efficiency of entrapment, particle size, and polydispersity index equal to 66.99±0.01%, 298.53 nm±12.04, and 0.323±0.01 respectively. Evaluation by using TEM and FTIR spectroscopy also confirmed the formation of spherical phytosome. There were no significant changes in the cream's organoleptic, pH, and viscosity during storage at room temperature. The permeation test through skin snake and Spangler’s membrane showed that cream containing phytosome had a better diffusion percentage than cream containing extract without phytosome technology. Conclusion: The results of this study showed that the antisolvent method was a potential method to develop phytosome of Phyllanthus emblica L. fruit extract and cream containing phytosome was effective in increasing the permeation.